The Impact of Monetary Policyon the Exchange Rate : Evidence From Three Small Open Economies - Zettelmeyer, Jeromin (IMF Working Papers; Working Paper, 2000)
This paper studies the impact effect of monetary policy shocks-identified by the reaction of three month market interest rates to policy announcements-on the exchange rate in Australia, Canada, and New Zealand during the 1990s. The main results are that (1) on average, a 100 basis point contractionary shock will appreciate the exchange rate by 2-3 percent on impact; (ii) seemingly 'perverse' reactions of the exchange rate to monetary policy are mainly attributable to reverse causality; (iii) in a few instances, there were true 'perverse' reactions of exchange rates to policy- generally, appreciations following expansionary shocks.